Giant linear magnetoresistance in half-metallic Sr2CrMoO6 thin films - Zhao-Cai Wang (Nature Portfolio, 2021)
Abstract Linear magnetoresistance (LMR) is a special case of a magnetic-field induced resistivity response, which has been reported in highly disordered semiconductor systems and in topological materials. In this work, we observe LMR effect in half-metallic perovskite Sr2CrMoO6 thin films, of which the maximum MR value exceeds +1600% at 2 K and 14 T. It is an unusual behavior in ferrimagnetic double perovskite material like Sr2CrMoO6, which are known for intrinsic tunneling-type negative magnetoresistance. In the thin films, the high carriers’ density (~1022 cm−3) and ultrahigh mobility (~104 cm2 V−1 s−1) provide a low-resistivity (~10 nΩ·cm) platform for spin-polarized current. Our DFT calculations and magnetic measurements further support the half-metal band structure. The LMR effect in Sr2CrMoO6 could possibly originate from transport behavior that is governed by the guiding center motion of cyclotron orbitals, where the magnetic domain structure possibly provides disordered potential. The ultrahigh mobility and LMR in this system could broaden the applications of perovskites, and introduce more research on metallic oxide ferri-/ferro-magnetic materials.